Kreator Meme dan Konstruksi Makna Meme Politik di Media Sosial - Rahmi Surya Dewi (Jurnal Komunikasi Global, 2019)
Meme, as part of visual communication, is happening during Jakarta's governor elections in 2017. The existence of the meme is not detached from the creativity of meme creators on social media. The research aims to reveal the characteristics of meme creators based on the type of meme and uncover the construction of meanings from the meme creator's viewpoints on Jakarta's governor election. This research used a qualitative method with a virtual ethnographic approach. Virtual ethnography is used to view visual phenomena or user culture in cyberspace. Data were collected in the form of meme posts, and user comments on the posts in Instagram accounts, interviews, and literature studies. The meme was analyzed using Van Dijk's critical discourse analysis focused on the social cognition section to observe the meaning of construction performed by the meme creator. The results showed that there are three characteristics of meme creators. Firstly, the meme creators who promote the candidate and counter the negative issue of the opposing party about the supported candidate. Secondly, they who provide the awareness of the community to be more critical and not easily deceived by negative symbols and issues. Thirdly, the chaotic creators who do not have a precise orientation in creating memes and upload memes just for jokes on social media.